Omnibus Law and the Paradox of Progress: A Critical Discourse Analysis of Labor Rights and Investment Flexibility in Post-Reform Indonesia - Wiraatma, Azzam Haidar; Anggraini, Kaylaresta Ratnadewi (Universitas Negeri Semarang, 2025)
This study examines the legislative discourse surrounding Indonesia’s Job Creation Law (Omnibus Law), focusing on the inherent tension between attracting foreign direct investment and upholding constitutional labor protections. Since the 1998 Reformation, Indonesia has struggled to balance neoliberal economic aspirations with social justice mandates. Utilizing Critical Discourse Analysis (CDA) on parliamentary debates, policy white papers, and judicial review transcripts, this research identifies a dominant narrative of